Lower pulmonary vein-to-left atrium volume ratio predicts poor rhythm outcome after atrial fibrillation catheter ablation - Lee, Jae-Hyuk; Hwang, Inseok; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2022)
Although left atrial (LA) dimension (LAD) is one of the predictors of atrial fibrillation (AF) recurrence after catheter ablation, repetitive recurrences occur in patients without enlarged LAD. We explored the predictive value of pulmonary vein (PV) to LA volume percent ratio (PV/LA%vol) for rhythm outcomes after AF catheter ablation (AFCA). We included 2913 patients (73.5% male, 60.0 [52.0–67.0] years old, 60.6% paroxysmal AF) who underwent AFCA. We evaluated the association between PV/LA%vol and AF recurrence after AFCA and compared the predictive value for AF recurrences according to the LA size with LAD. We additionally investigated the association between PV/LA%vol and PITX2 gene using a genome-wide association study. LAD affected 1-year recurrence only in the highest tertile group (T3, p = 0.046), but PV/LA%vol determined 1-year recurrence in all LAD groups (T1, p = 0.044; T2, p = 0.021; and T3, p = 0.045). During 20.0 (8.0–45.0) months of follow-up, AF recurrence rate was significantly higher in patients with lower PV/LA%vol (Log-rank p = 0.004, HR 0.91 [0.84–1.00], p = 0.044). In the T1 and T2 LAD groups, predicting AF recurrences was better with PV/LA%vol than with LAD (AUC 0.63 vs. 0.51, p < 0.001 at T1; AUC 0.61 vs. 0.50, p = 0.007 at T2). We replicated PITX2-related rs12646447, which was independently associated with PV/LA%vol (β = 0.15 [0–0.30], p = 0.047). In conclusion, smaller PV volumes after LA volume adjustments have genetic background of PITX2 gene and predictive value for poorer rhythm outcomes after AFCA, especially in patients without LA enlargement.